Cognitive links between mountains and lowlands: balance weights from the Early Bronze Age site of Shengavit (Armenia) in context - Simonyan, Hakob; Gevorgyan, Aram; Bobokhyan, Arsen (ARAMAZD: Armenian Journal of Near Eastern Studies, 2019)
The timespan from the mid 4th to the mid 3rd millennium BC is characterised by essential social transformations in the Near East and surrounding regions. The growing complexity is reflected, among others, also in technological innovations and active trade relations, which led to the appearance of balance weights and corresponding weight systems. This contribution, based on evidence from the settlement of Shengavit, Armenia, argues that balance weights were in use also beyond Mesopotamia, within the area of the spreading of Kura-Araxes cultural community, from the southern Caucasus to the Fertile Crescent. The use of such weight systems at Kura-Araxes sites implies possible cognitive links to the Near Eastern centres, reflecting the transfer of knowledge between mountains and lowlands.